EPHA mutation as a predictor of immunotherapeutic efficacy in lung adenocarcinoma - Xin Wang; Li Zhang; Jie Wang; Jing Sun; Yu Xu; Zhijie Wang; Hua Bai; Jianchun Duan; Wenfeng Fang; Guoqiang Wang; Rui Wan; Jiachen Xu; et al. (Journal for ImmunoTherapy of Cancer)
Background Ephrin type-A receptors (EPHA) are members of family of receptor tyrosine kinases and are related to tumor immunogenicity and immune microenvironment, however, the association between EPHA mutation (EPHAmut) and efficacy of immune checkpoint inhibitors (ICIs) has not been investigated in non-small cell lung cancer (NSCLC).Methods Multiple cohorts were used to assess the immunotherapeutic predictive performance of EPHAmut, including one discovery cohort (n=79) and two public validation cohort (cohort 1: NSCLC, n=165; cohort 2: pan-cancer, n=1662). The Cancer Genome Atlas cohort was used for prognostic analysis and mechanism exploration.Results In the discovery cohort, patients with EPHAmut had superior disease control rate (72.2% vs 36.1%, p=0.01) and progression-free survival (PFS) (HR 0.38; 95% CI 0.21 to 0.68; p<0.001) compared with those with wide-type EPHA (EPHAwt) in NSCLC. The association between EPHAmut and immunotherapy outcomes in NSCLC was consistently observed in the validation cohorts by multivariable models (cohort 1, PFS HR 0.59; 95% CI 0.37 to 0.96; p=0.03; cohort 2, overall survival (OS) HR 0.63; 95% CI 0.41 to 0.98; p=0.04). Further pooled estimates of the discovery and validation cohorts showed that patients with EPHAmut exhibited a significantly longer PFS and OS in lung adenocarcinoma (LUAD) while not squamous cell lung cancer (LUSC). Consistently, mechanism analysis revealed that patients with EPHAmut was associated with increased T cell signatures and downregulated transforming growth factor-β signaling compared with patients with EPHAwt in LUAD while not LUSC.Conclusions Our results demonstrated that EPHAmut is an independent classifier that could stratify patients with LUAD for ICIs therapy. Further prospective studies are warranted.Trial registration number NCC2016JZ-03, NCC2018-092.